2009
DOI: 10.1007/s00056-009-9915-0
|View full text |Cite
|
Sign up to set email alerts
|

Torque Stability of Plastic Brackets Following Multiple Loading and Artificial Material Aging – an In-Vitro Comparison

Abstract: Each bracket material requires its own torque value to transfer identical torque values onto the tooth in clinical practice. Comparison with steel brackets revealed that only plastic brackets with a metal slot are suitable for clinical use. Adding ceramic and glass fibers to polycarbonate, or using polyurethane has no benefit in terms of torque stability. In addition, after a single application of torque, all brackets lose torque stability in response to a renewed load.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
(50 reference statements)
0
8
1
Order By: Relevance
“…A comparison between metal, ceramic, and plastic brackets has shown that slot wall rigidity varied according to the material. Low rigidity brackets such as plastic, and to a lesser degree, metallic ones, allowed more play for the wire than rigid ceramic brackets (Harzer, Bourauel, & Gmyrek, 2004;Matsui, Umezaki, Komazawa, Otsuka, & Suda, 2015;Möller, Klocke, Sadat-Khonsari, Schlegel, & Kahl-Nieke, 2009;Morina, Eliades, Pandis, Jäger, & Bourauel, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A comparison between metal, ceramic, and plastic brackets has shown that slot wall rigidity varied according to the material. Low rigidity brackets such as plastic, and to a lesser degree, metallic ones, allowed more play for the wire than rigid ceramic brackets (Harzer, Bourauel, & Gmyrek, 2004;Matsui, Umezaki, Komazawa, Otsuka, & Suda, 2015;Möller, Klocke, Sadat-Khonsari, Schlegel, & Kahl-Nieke, 2009;Morina, Eliades, Pandis, Jäger, & Bourauel, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…14 This was assumed to have a negative effect in the torque capacity of polycarbonate brackets and led various laboratory studies to suggest that plastic brackets without a metal slot are inappropriate to deliver the desirable amount of torque in clinical conditions. [15][16][17] The problem was considered even greater for plastic brackets filled with ceramic particles, 17 as those examined in our case. However, such an effect was not evident in our study.…”
Section: Discussionmentioning
confidence: 94%
“…This difference in fracture load values can be explained by difference in material characteristics of the brackets used. [12][13][14][15] In a clinical situation, the torquing moment transferred from the wire to the maxillary central incisor was 1035 to 2373 gfmm. [16][17][18] Therefore, results of this study indicate that all brackets tested have enough resistance to deformation or fracture to incorporate torque to the maxillary central incisor using 0.019 × 0.025˝ SS archwire.…”
Section: Discussionmentioning
confidence: 99%